Transcriptomics in Erigeron canadensis reveals rapid photosynthetic and hormonal responses to auxin herbicide application. (12th March 2020) - McCauley, Cara L; McAdam, Scott A M; Bhide, Ketaki; Thimmapuram, Jyothi; Banks, Jo Ann; Young, Bryan G
Abstract : Auxin herbicides trigger a rapid down-regulation of photosynthetic-related gene expression and an up-regulation of abscisic acid biosynthesis independent of other plant hormones in Erigeron . Abstract: The perception pathway for endogenous auxin has been well described, yet the mode of action of synthetic auxin herbicides, used for >70 years, remains uncharacterized. We utilized transcriptomics and targeted physiological studies to investigate the unknown rapid response to synthetic auxin herbicides in the globally problematic weed species Erigeron canadensis . Synthetic auxin herbicide application consistently and rapidly down-regulated the photosynthetic machinery. At the same time, there was considerable perturbation to the expression of many genes related to phytohormone metabolism and perception. In particular, auxin herbicide application enhanced the expression of the key abscisic acid biosynthetic gene, 9-cis-epoxycarotenoid deoxygenase ( NCED ). The increase in NCED expression following auxin herbicide application led to a rapid biosynthesis of abscisic acid (ABA). This increase in ABA levels was independent of a loss of cell turgor or an increase in ethylene levels, both proposed triggers for rapid ABA biosynthesis. The levels of ABA in the leaf after auxin herbicide application continued to increase as plants approached death, up to >3-fold higher than in the leaves of plants that were drought stressed. We propose a new model in which synthetic auxin herbicides trigger plant death by the whole-scale, rapid, down-regulation of photosynthetic processes and an increase in ABA levels through up-regulation of NCED expression, independent of ethylene levels or a loss of cell turgor.